Reputation system of C2C e-commerce, buying interest and trust - Linda Kusuma; Sri Rejeki; Robiyanto Robiyanto; Lala Irviana (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
One form of the development of technology and internet users in Indonesia is the merge of various C2C (Customers to Customers) e-commerce on the marketplace. Bukalapak is one of the examples. This research presents the effects of reputation systems on trust, trust in buying interest, and reputation systems on Bukalapak customers' buying interests. A total of 120 respondents participated and the data were analyzed using structural equation modeling with Amos 20 software. The results show that the reputation system has a higher direct impact compared to the impacts mediated by trust. Therefore, in an effort to increase the buying interest, the sellers should increase their reputation in the reputation system represented in the list of feedback, review, and the badge level in Bukalapak. To marketplace providers, in this case, Bukalapak, there is still a need to increase the customers' trust. Although it is significant, however, it has low impacts both directly and indirectly.
Keywords: M10; M21; M15; 650; C2C marketplace; reputation systems; trust; buying interest; Bukalapak